Challenges of implementing the accreditation model in military and university hospitals in Iran: a qualitative study - Leila Vali; Mohammad Hossein Mehrolhasani; Saeid Mirzaei; Nadia Oroomiei (BMC, 2020)
Abstract Background The aim of this study was to present challenges of implementing the accreditation model in university and military hospitals in Iran. Methods In this qualitative study, purposive sampling was used to select hospital managers and implementers of the model working in 3 hospitals affiliated to Kerman University of Medical Sciences and in 3 military hospitals in Kerman, Iran. A total of 39 participants were interviewed, and semi-structured questionnaires and thematic analysis were used for data collection and analysis, respectively. Results In this study, 5 major codes and 17 subcodes were identified: (1) perspectives on accreditation model with 5 subcodes: a difficult and time-consuming model, less attention to the patient, accreditation as a way of money acquisition, not being cost-effective, and accreditation means incorrect documentation; (2) absence of appropriate executive policy, with 3 subcodes: lack of financial funds and personnel, disregarding local conditions in implementation and evaluation, and absence of the principle of unity of command; (3) training problems of the accreditation model, with 2 subcodes: absence of proper training and incoordination of training and evaluation; (4) human resources problems, with 3 subcodes: no profit for nonphysician personnel, heavy workload of the personnel, and physicians' nonparticipation; (5) evaluation problems, with 4 subcodes: no precise and comprehensive evaluation, inconformity of authorities' perspectives on evaluation, considerable change in evaluation criteria, and excessive reliance on certificates. Conclusions This study provided useful data on the challenges of implementing hospitals' accreditation, which can be used by health policymakers to revise and modify accreditation procedures in Iran and other countries with similar conditions. The accreditation model is comprehensive and has been implemented to improve the quality of services and patients' safety. The basic philosophy of hospital accreditation did not fully comply with the underlying conditions of the hospitals. The hospital staff considered accreditation as the ultimate goal rather than a means for achieving quality of service. The Ministry of Health and Medical Education performed accreditation hastily for all Iranian hospitals, while the hospitals were not prepared and equipped to implement the accreditation model.